Architectural implications of colonial infrastructure (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The Dutch East Indies' colonial infrastructure, particularly Java's railway network and its linkages to sugar fields and mills, changed urban and economic environments. Railways, originally designed for military defense in the 1840s, became economic arteries supporting agro-industrial growth under the Cultuurstelsel (1830) and Agrarian Law (1870), according to historical data. Strategic railway planning promotes resource extraction, urban expansion, and path dependence, sustaining urban centers after colonialism. Synchronic-diachronic and network analysis compare the phased development of railway stations and sugar mills (1830–1942), examining shared architectural influences, materials (from local wood to imported steel), and styles (pragmatic neoclassical to Indies and Art Deco). Railways efficiently transported sugarcane and cargo, while mills incorporated rail lines, creating divided towns and industrial landscapes. Technical adaptations to tropical temperatures and commercial incentives show how colonial exploitation shaped Java's spatial character. This study illuminates how colonial infrastructure, architectural rationalism, and economic imperatives shaped Java's modern landscape, enriching historical studies.
Keywords: Colonial infrastructure; Dutch East Indies; Railway station; Sugar plantations; Spatial development